2021
DOI: 10.1128/jb.00454-20
|View full text |Cite
|
Sign up to set email alerts
|

Gut Microbiota: the Emerging Link to Lung Homeostasis and Disease

Abstract: The gut microbiota plays a crucial role in the development of the immune system and confers benefits or disease susceptibility to the host. Emerging studies have indicated that the gut microbiota could affect pulmonary health and disease through cross-talk between the gut microbiota and the lungs. Gut microbiota dysbiosis could lead to acute or chronic lung disease, such as asthma, tuberculosis and lung cancer. In addition, the composition of the gut microbiota may be associated with different lung diseases, t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
28
0
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 45 publications
(32 citation statements)
references
References 98 publications
1
28
0
3
Order By: Relevance
“…Additionally, S24_7 (Muribaculaceae) beneficial bacteria, were seen both in the lungs and the gut of the SEB + AEA group. These findings supported the concept of crosstalk between gut and lung microbiomes [ 71 , 72 , 73 ]. Our study also indicated that AEA treatment led to a decrease in the abundance of the order Pseudomonas and Caulobacterlaes, which are both believed to cause human respiratory tract infections [ 38 , 74 ].…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, S24_7 (Muribaculaceae) beneficial bacteria, were seen both in the lungs and the gut of the SEB + AEA group. These findings supported the concept of crosstalk between gut and lung microbiomes [ 71 , 72 , 73 ]. Our study also indicated that AEA treatment led to a decrease in the abundance of the order Pseudomonas and Caulobacterlaes, which are both believed to cause human respiratory tract infections [ 38 , 74 ].…”
Section: Discussionsupporting
confidence: 86%
“…Additionally, many recent studies demonstrate the importance of the gut microbiome in modulating immune responses and changes in the gut microbiota alter immune responses and homeostasis in the respiratory system [22]. It is surmised that this cross-talk occurs through the production of metabolites, endotoxins and cytokines by the gut microbiota which travel to the respiratory mucosa through the bloodstream [23]. Some more recent studies suggest that this cross-talk is bidirectional, with the lung microbiota potentially mediating immunologic responses in the gut [24,25].…”
Section: The Lung Microbiome and Lung Cancermentioning
confidence: 99%
“…However, the beta diversity analysis showed a significant difference in the microbial composition ( Figure 2 ). It has been reported that the gut microbial composition in healthy humans is significantly different from that in patients with cancers, including lung cancer [ 25 , 41 , 42 ]. Therefore, an alteration of the gut microbiota composition appears to be significantly influential on carcinogenesis in the lung.…”
Section: Discussionmentioning
confidence: 99%